A numerical tool for flow simulation in a Wankel motor - Rannacher, Rolf; Heuveline, Vincent (Mathematics - key technology for the future, 2003)
We describe the main steps in the development of a new numerical tool for simulating gas flow and heat transfer in a rotary engine (“Wankel motor”). Our approach comprises a 2D/3D grid generator for the Wankel motor geometry, an implicit finite element discretization for coping with the stiff pressure-velocity coupling and robust multigrid solvers on strongly distorded meshes. These components are implemented within a new FE-software package named Hi-Flow++ which is presently under development.
Gesehen am 20.08.2018